The Design and Implementation of EANSS Model for Antivirus Software Protection - LIU Xin; SONG Xian-hua; WU Shi-peng; LI Zeng-guang; ZHANG Huan; WANG Kai (Journal of Harbin University of Science and Technology)
Aiming at ANSS( ANtivirus Software Shield) model disadvantages，this paper extends ANSS model and proposes a new model named EANSS( Enhanced ANtivirus Software Shield) ． There are some new rules of the attack are added into the new model，and the real-time monitoring mechanism and the self learning mechanism also be joined in the ENASS model to improve the ability of protection． Experiment results show that the EANSS model not only don’t influences the operations of normal applications but also can protect antivirus software from being terminated by them with low CPU performance overhead and memory write performance overhead．